Contributions to the taxonomy, identification, and biogeography of the Western Palaearctic species of Campoletis Förster (Ichneumonidae: Campopleginae) - Vas, Zoltán (Zootaxa, 2019)
Two new species of Campoletis Förster (Ichneumonidae: Campopleginae) are described: Campoletis katalinarum sp. nov. from Georgia and Turkey, and Campoletis margaritae sp. nov. from Romania and Armenia. Affixes to the identification key of the most recent revision of the genus are given. Additionally, contributing to the knowledge on biogeographical distribution of several species of the genus, 27 new records of 14 Campoletis species are reported, representing first records for 12 countries in the Palaearctic region.